PENGARUH JOB COMPETENCE, JOB LOYALTY DAN JOB CULTURE TERHADAP EMPLOYEE PRODUCTIVITY PADA PT. TELKOM WITEL SUMATERA (MEDAN) - Sri Ayu Novalina Pardosi; Sondang N.B Marbun; Mislan Sihite (Jurnal Pijar, 2026)
This study aims to analyze the effect of job competence, job loyalty, and job culture on employee productivity at PT. Telkom Witel Sumatera (Medan). This study uses a quantitative approach with a survey method. The population in this study was all employees of PT. Telkom Witel Sumatera (Medan), with a sample size of 32 respondents determined using saturated sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the help of the SPSS program. The results showed that job competence had a significant partial effect on employee productivity with a t- value of 4.764 and a significance of 0.000. Job loyalty also has a significant effect on employee productivity with a t-value of 2.536 and a significance of 0.017. Furthermore, job culture has a significant effect on employee productivity with a t-value of 4.312 and a significance of 0.000. Simultaneously, job competence, job loyalty, and job culture had a positive and significant effect on employee productivity with a calculated F value of 31.907 and a significance level of 0.000. The coefficient of determination value shows that 76.2% of the variation in employee productivity was influenced by these three variables, while the rest was influenced by other factors outside the scope of this study. The results of this study are expected to be taken into consideration by companies in improving employee productivity through the sustainable management of competencies, loyalty, and work culture.